The “amphi”-brains of amphipods: new insights from the neuroanatomy of Parhyale hawaiensis (Dana, 1853) - Christin Wittfoth; Steffen Harzsch; Carsten Wolff; Andy Sombke (Frontiers in Zoology, 2019)
Abstract Background Over the last years, the amphipod crustacean Parhyale hawaiensis has developed into an attractive marine animal model for evolutionary developmental studies that offers several advantages over existing experimental organisms. It is easy to rear in laboratory conditions with embryos available year-round and amenable to numerous kinds of embryological and functional genetic manipulations. However, beyond these developmental and genetic analyses, research on the architecture of its nervous system is fragmentary. In order to provide a first neuroanatomical atlas of the brain, we investigated P. hawaiensis using immunohistochemical labelings combined with laser-scanning microscopy, X-ray microcomputed tomography, histological sectioning and 3D reconstructions. Results As in most amphipod crustaceans, the brain is dorsally bent out of the body axis with downward oriented lateral hemispheres of the protocerebrum. It comprises almost all prominent neuropils that are part of the suggested ground pattern of malacostracan crustaceans (except the lobula plate and projection neuron tract neuropil). Beyond a general uniformity of these neuropils, the brain of P. hawaiensis is characterized by an elaborated central complex and a modified lamina (first order visual neuropil), which displays a chambered appearance. In the light of a recent analysis on photoreceptor projections in P. hawaiensis, the observed architecture of the lamina corresponds to specialized photoreceptor terminals. Furthermore, in contrast to previous descriptions of amphipod brains, we suggest the presence of a poorly differentiated hemiellipsoid body and an inner chiasm and critically discuss these aspects. Conclusions Despite a general uniformity of amphipod brains, there is also a certain degree of variability in architecture and size of different neuropils, reflecting various ecologies and life styles of different species. In contrast to other amphipods, the brain of P. hawaiensis does not display any striking modifications or bias towards processing one particular sensory modality. Thus, we conclude that this brain represents a common type of an amphipod brain. Considering various established protocols for analyzing and manipulating P. hawaiensis, this organism is a suitable model to gain deeper understanding of brain anatomy e.g. by using connectome approaches, and this study can serve as first solid basis for following studies.